Secondary interactions arrest the hemiaminal intermediate to invert the modus operandi of schiff base reaction: a route to benzoxazinones - Patel, Ketan; Deshmukh, Satej S.; Bodkhe, Dnyaneshwar; Mane, Manoj; Vanka, Kumar; Shinde, Dinesh; Rajamohanan, Pattuparambil R.; Nandi, Shyamapada; Vaidhyanathan, Ramanathan; Chikkali, Samir H. (Journal of Organic Chemistry, 2017)
Discovered by Hugo Schiff, condensation between amine and aldehyde represents one of the most ubiquitous reactions in chemistry. This classical reaction is widely used to manufacture pharmaceuticals and fine chemicals. However, the rapid and reversible formation of Schiff base prohibits formation of alternative products, of which benzoxazinones are an important class. Therefore, manipulating the reactivity of two partners to invert the course of this reaction is an elusive target. Presented here is a synthetic strategy that regulates the sequence of Schiff base reaction via weak secondary interactions. Guided by the computational models, reaction between 2,3,4,5,6-pentafluoro-benzaldehyde with 2-amino-6methylbenzoic acid revealed quantitative (99%) formation of 5-methyl-2-(perfluoropheny01,2-dihydro-4H-benzo[d][1,3]oxazin-4-one (15). Electron donating and electron withdrawing ortho-substituents on 2-aminobenzoic acid resulted in the production of benzoxazinones 936. The mode of action was tracked using low temperature NMR, IN vis spectroscopy, and isotopic (O-18) labeling experiments. These spectroscopic mechanistic investigations revealed that the hemiaminal intermediate is arrested by the hydrogen-bonding motif to yield benzoxazinone. Thus, the mechanistic investigations and DFT calculations categorically rule out the possibility of in situ imine formation followed by ring-closing, but support instead hydrogen-bond assisted ring-closing to prodrugs. This unprecedented reaction represents an interesting and competitive alternative to metal catalyzed and classical methods of preparing benzoxazinone.

Emerging trends in olefin polymerization: a perspective - Birajdar, Rajkumar S.; Bodkhe, Dnyaneshwar; Gupta, Poonam; Shaikh, Maulali H.; Ramekar, Rohan; Chikkali, Samir H. (Journal of macromolecular science part A- pure and applied chemistry, 2023)
The seemingly matured field of olefin polymerization still poses several challenges and holds enormous potential to meet contemporary material requirements. In this feature article, we examine the progress of olefin polymerization in the last two decades. Among the several emerging trends, we identify four most impactful discoveries, namely, (i) disentangled ultra-high molecular weight polyethylene (dUHMWPE), (ii) disubstituted functional olefin copolymerization, (iii) incorporation of bioderived comonomers in polyolefins, and (iv) application of above (ii, iii) functional polyolefins as compatibilizers. The dUHMWPE has attracted significant attention and heterogeneous Ziegler-type catalysts, homogenous metallocene, and post-metallocene catalysts have been reported to produce disentangled ultrahigh molecular weight polyethylene. Insertion copolymerization of difunctional disubstituted olefins has been reported only recently and ortho-phosphinobenzene sulfonate palladium catalyst outperforms the other catalysts. Interestingly, insertion copolymerization of bioderived olefins has witnessed a surge in the number of reports. Sugar and plant oil-derived olefins have been copolymerized with ethylene to obtain relatively hydrophilic polyethylene. The functional polyethylene is finding a new application as compatibilizer or displays better adhesion to surfaces. Thus, the feature article offers a succinct account of emerging trends in polyolefins, identifies the most impactful contributions, and debates the application potential of these new materials.
Keywords: compatibilizer; Functional polyethylene; Insertion (co)polymerization; renewable monomers; uHMWPE